Episodic focus formulation in media scholars’ data interaction - Laura Korkeamäki; Heikki Keskustalo; Sanna Kumpulainen (Information Research: An International Electronic Journal)
Introduction. Focus formulation affects task information interaction and task performance. It has typically been conceptualised as one task stage in the overall task performance. Nevertheless, we take a different approach by studying focus formulation as an episodic phenomenon in the task process performance. Episodic focus formulation includes several focus formulation episodes during task performance processes that gradually lead to focus, but instead of considering the larger task, this happens during a subtask. The purpose of this study is to examine what is episodic focus formulation like in media scholars’ data interaction.